2021
DOI: 10.1364/ol.419790
|View full text |Cite
|
Sign up to set email alerts
|

High-harmonic-driven inverse Raman scattering

Abstract: Spectral analysis of high-order harmonics generated by ultrashort mid-infrared pulses in molecular nitrogen reveals well-resolved signatures of inverse Raman scattering, showing up near the frequencies of prominent vibrational transitions of nitrogen molecules. When tuned on a resonance with the v ′ = 0 → v ′ ′ = 0 pathway within the B 3 Π g → C 3 Π … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…For the increased versatility of being able to use either a red-shifted or a blue-shifted probe to mitigate possible issues with sample absorption (Figure S1 and Table S1), we seek to investigate the feasibility of using a modified version of SRDM, based on inverse Raman spectroscopy (IRS). IRS, similar to SRS, generates a signal through the use of a pump pulse and a shifted-probe pulse. However, instead of using a red-shifted probe, IRS uses a blue-shifted probe.…”
Section: Introductionmentioning
confidence: 99%
“…For the increased versatility of being able to use either a red-shifted or a blue-shifted probe to mitigate possible issues with sample absorption (Figure S1 and Table S1), we seek to investigate the feasibility of using a modified version of SRDM, based on inverse Raman spectroscopy (IRS). IRS, similar to SRS, generates a signal through the use of a pump pulse and a shifted-probe pulse. However, instead of using a red-shifted probe, IRS uses a blue-shifted probe.…”
Section: Introductionmentioning
confidence: 99%
“…The self-compression can also happen in air under conditions of no ionization. Utilizing the anomalous dispersion of air in the wavelength range from 3.5 to 4.2 μm, soliton self-compression of high peak power pulses were achieved by loosely focusing in air [67]. In this work, the strong HOD near the edge of the CO2 absorption band also affects the soliton dynamics.…”
Section: Koprinkov Et Al Observed Self-compression Of High-intensity ...mentioning
confidence: 98%
“…Mitrofanov et al demonstrated that high peak power MIR pulses can be soliton selfcompressed during free propagation within the regions of anomalous dispersion in air to yield few-cycle sub-terawatt field waveforms [67]. Although the input peak power is estimated to be larger than the critical power, they confirmed that there were no filamentations happening and explained the self-compression by soliton dynamics with influence of HOD.…”
Section: Mechanisms Behind Laser Pulse Self-compressionmentioning
confidence: 99%
See 1 more Smart Citation